Electrically evoked compound action potential recording in peripheral nerves. Issue 1 (January 2018) - Parker, John L; Shariati, Nastaran H; Karantonis, Dean M
Applications for bioelectric medicine can be found in all parts of the nervous system. The CNS – brain and spinal cord – contain targets for commercial neuromodulation therapies. Peripheral nerves are also modulated with commercially available systems during treatment for chronic pain and epilepsy, and developments are in progress for treating many other diseases. The electrically evoked compound action potential is a measure of the electrical response from the tissue to stimulation. It provides a direct insight into the electrophysiology of the stimulation, and despite its incorporation into cochlear implants it is a technology that is yet to find its way into commercial peripheral nerve stimulation applications. This review outlines the status of evoked compound action potential measurements on peripheral nerves and highlights the challenges which need to be overcome.